A case report: melanotic neuroectodermal tumor of infancy: diagnose and treatment - Hao, Tran Kiem; Loi, Nguyen Hong; Duy, Phan Canh; Hoa, Nguyen Thi Kim; Phu, Tran Xuan; Khanh, Nguyen Van; Thach, Hoang Ngoc (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.